Effects of Di (2-ethylhexyl) phthalate on sperm morphology of Wistar rats (Indian Journal of Veterinary Pathology, 2026)
Phthalate extensively used as plasticizers in medical devices, cosmetics, children’s toys, deodorants and other industries, which is a major environmental toxicant. As they are not covalently bound to polymers and leach easily into the environment and cause a significant health risk. Hence, the present study was carried out to evaluate the effects of Di (2-ethyl hexyl) phthalate on sperm morphology in Wistar rats. Animals were exposed to DEHP at 100, 200 and 400 mg/kg b.wt in corn oil for a period of 28 days. Animals were sacrificed on 29th day and semen was collected from the cauda epididymis and stained with eosin (5%) and nigrosine (10%) staining. Results of this study revealed more sperm abnormalities in all DEHP-exposed groups with more pronounced abnormalities in the high dose group. A highly significant (P